The Impact of M&A on the Financial Performance of Banks in Kazakhstan - Shaikenova, G.; Tursynbek, A. (International School of Economics Maqsut Narikbayev University, Astana, 2024)
Nowadays, M&A activity has become an increasingly prominent strategic tool for growth and competitiveness within the banking sector in Kazakhstan, driven by evolving regulations and market conditions. The current study investigates the impact of M&A on the financial performance of selected banks in Kazakhstan from 2013 to 2023. A quantitative, non-experimental methodology was used to utilize historical M&A transactions data in the banking industry in Kazakhstan within recent 10 years and accounting data of selected 9 banks. 3 years preceding and following M&A transaction completion year were analyzed for each bank by conducting a financial ratio analysis and a paired sample t-test. It was hypothesized that there is either significant or no significant difference between pre-M&A and post-M&A profitability, liquidity and leverage ratios of the banking sector and banks on an individual basis. The findings revealed that M&A had a slight positive impact on liquidity ratios and no impact on profitability and leverage ratios of the overall banking sector in the selected post-M&A period. The results showed that M&A had a minor influence on banks’ financial indicators on an individual basis within 3 years after M&A date. This study contributes to the extension of knowledge about M&A activities in emerging markets by offering an analysis in the case of Kazakhstan’s banking sector. The scope of this study was limited in terms of the availability of financial data published by banks and information in LSEG Workspace, which impacted the selected time frame for analysis. The research was conducted only for the banking sector in Kazakhstan.
Keywords: Mergers and acquisitions (M&A), banking sector, financial ratio analysis, paired sample t-test